The trajectory to elite level: An investigation of the individual and environmental features of within career transitions in sport - Andronikos, G. (2018)
While much of the `sport transitions` literature focusses on the `end of career`, research focussing on within career transitions in sport has identified a number of challenging transitions, for example, the move from junior to senior sport. While there is some very focussed (e.g., Scandinavian context) quantitative research that has been conducted, our understanding regarding the factors that contribute to the adjustment of athletes through within career sport transitions is mainly based from qualitative methodologies. It is clear that there are a number of important transitions on the path to elite sport, which may vary depending on factors such as sport and culture (e.g. diversification to specialising; junior to senior; academy to professional; elite to super elite; continued longevity of success). Continuing to broaden and deepen our understanding in this area will help both researchers and practitioners working with athletes on this pathway. As such, the objectives of this thesis are to: 1) Understand the predictive factors of adjustment and satisfaction through important within career sport transitions; 2) Investigate the individual, environmental and experiential features that are associated with successful and unsuccessful transitions to elite level sport 3) Investigate the individual characteristics and environmental features of a highly successful world class elite development program. These three thesis objectives were achieved through four aims and associated studies. Specifically: a) Examining the junior to senior transition experiences of a cross-cultural population using the Transition Monitoring Survey, b) Examining the individual and environmental characteristics, and developmental experiences of athletes who successfully negotiated the transition to elite level through qualitative methodology, c) Examining the individual and environmental characteristics, and developmental experiences of athletes who were unsuccessful in negotiating the transition to elite level, through qualitative methodology, and d) Examining the mechanisms that underpin the success of an independent triathlon program in developing elite world-class level athletes, using a qualitative approach. Subtleties of the trajectory were identified and interestingly athletes who successfully progressed to elite level made a choice to commit to their sport after taking part in deliberate play activities during early steps. On the contrary, unsuccessful athletes specialized early and in some cases the sport they were involved was not a personal choice. Findings showed that a combination of individual and environmental characteristics is necessary in order to cope successfully with within-career transitions. Physical abilities, commitment, motivation, aspirations, mental skills and the ability to respond to challenges were acknowledged as facilitators of a successful trajectory towards elite level. As environmental features also play a significant role in the outcome of the within career transitions an environment focused on long-term development, with clear and coherent communication and goals promoting the athlete wellbeing while in the same time utilizing intentional challenge can facilitate the pathway to elite level. The integration of the selection process as part of the talent development and the use of role models within the team to enable individuals continuously learn from each other were additional features identified. On the other hand, social pressure, balancing a dual career, a winning focused environment and poor communication were the main barriers that may lead to dropout. Practical implications are that increasing the quality of athletes` preparation and equipping them with the skills and attributes required in order to cope with the challenges of the within career transitions during their trajectory to elite level competition would facilitate progression. As such, not only developing individual characteristics but also creating an environment that aids to this end would increase the chances of athletes reach at elite level. Research implications of this thesis are that key individual and environmental features that facilitate progression to elite level were identified. Future research is required regarding the potential connection of early experiences and long-term achievements in sport, differences between team and individual sports while also further examination of successful environments and longitudinal examination of within career transitions.